A bimodule description of the Hecke category. (30th October 2021) - Abe, Noriyuki
Abstract: For a Coxeter system and a representation $V$ of this Coxeter system, Soergel defined a category which is now called the category of Soergel bimodules and proved that this gives a categorification of the Hecke algebra when $V$ is reflection faithful. Elias and Williamson defined another category when $V$ is not reflection faithful and proved that this category is equivalent to the category of Soergel bimodules when $V$ is reflection faithful. Moreover, they proved the categorification theorem for their category with fewer assumptions on $V$ . In this paper, we give a bimodule description of the Elias–Williamson category and re-prove the categorification theorem.